Actuality of experience study of non-philological disciplines future teachers' foreign-languages training in higher schools of Poland and Czech Republic - Gromov Yevhen (Borys Grinchenko Kyiv Metropolitan University, 2017)
The author asserts that realization of principal theses of pan-European recommendations for linguistic education stipulates necessity to revise settled views on the process of future teachers' foreign-languages preparation taking into account modern society demands and requirements on level and extent of knowledge which every higher pedagogical institution graduate must possess. Thus we face the pressing demand of making adjustment of future pedagogues' linguistic training in correspondence to actual challenges which presume conversion from traditional to innovative methods of individuals' professional formation, from priorities of narrowly specialized tasks to holistic development of future teachers, pedagogical interaction, joint creativity and cooperation which provide Ukraine's integration into European educational space. It has been supposed in the article that investigation of modern tendencies in foreign-languages training of non-philological disciplines future teachers in higher schools of Poland and Czech Republic is an actual pedagogical problem. Main directions of possible scientific research have been outlined; unsolved aspects, principle objectives, methodological groundings, research approaches, as well as practical and theoretical importance for native pedagogical science have been determined. It has been shown that scientific investigations which are aimed at ascertainment of basic peculiarities of non-philological teachers' professional formation in conditions of united European educational space formation will designate further perspectives for implementation of Eastern-European countries positive experience into Ukrainian pedagogical practice.